IMPLEMENTASI AI DALAM PENERAPAN TOPOLOGI JARINGAN STUDI KASUS DI SMPN 2 WONOSOBO - Pramudella Fikar, Wahyu; Wijayanto, Wijayanto; Ricky Rozaqqi, Ade (Penerbit Lafadz Jaya, 2025)
The advancement of digital education demands reliable, efficient, and easily managed network infrastructure. This study discusses the implementation of Artificial Intelligence (AI) to determine the optimal network topology design for the computer laboratory at SMP Negeri 2 Wonosobo, which consists of 30 PCs, a 50 Mbps internet connection, and all devices located on the second floor. A descriptive case study method was employed, involving field observations, interviews, technical measurements, and simulations using Cisco Packet Tracer. AI was utilized to analyze network requirements, including the number of devices, usage patterns, and room layout, in order to generate recommendations for network topology, IP address configuration, QoS settings, and cost estimation. The simulation results indicate that the AI-generated design can be effectively implemented with minor adjustments to available equipment, such as using two 24-port switches as an alternative to a 48-port switch. This implementation provides stable connectivity and efficient network management, making it a viable reference for future network development or improvement in schools.